Forty years of research on personality in software engineering: A mapping study. - Cruz, Shirley; da Silva, Fabio Q.B.; Capretz, Luiz Fernando (Computers in Human Behavior, 2015)
In this article, we present a systematic mapping study of research on personality in software engineering. The goal is to plot the landscape of current published empirical and theoretical studies that deal with the role of personality in software engineering. We applied the systematic review method to search and select published articles, and to extract and synthesize data from the selected articles that reported studies about personality. Our search retrieved more than 19,000 articles, from which we selected 90 articles published between 1970 and 2010. Nearly 72% of the studies were published after 2002 and 83% of the studies reported empirical research findings. Data extracted from the 90 studies showed that education and pair programming were the most recurring research topics, and that MBTI was the most used test. Research related to pair programming, education, team effectiveness, software process allocation, software engineer personality characteristics, and individual performance concentrated over 88% of the studies, while team process, behavior and preferences, and leadership performance were the topics with the smallest number of studies. We conclude that the number of articles has grown in the last few years, but contradictory evidence was found that might have been caused by differences in context, research method, and versions of the tests used in the studies. While this raises a warning for practitioners that wish to use personality tests in practice, it shows several opportunities for the research community to improve and extend findings in this field.